Enhancement the Sensitivity of waveguide Coated ZnO thin films: Role of Plasma irradiation - Younus, Marwan Hafeedh; Ahmed, Muayad Abdullah; Ali, Ghazwan Ghazi (Iraqi Journal for Electrical and Electronic Engineering, 2020)
In this study, Dielectric Barrier Discharge plasma irradiation (DBD) is applied to treatment and improve the properties of the ZnO thin film deposited on the glass substrate as a sensor for glucose detection. The ZnO is prepared via a sol-gel method in this work. ZnO is irradiated by the DBD high voltage plasma to improve of its sensitivity. The optical properties, roughness and surface morphology of the waveguide coated ZnO thin films before and after DBD plasma irradiation are studied in this work. The results showed a significant improvement in the performance of the sensor in the detection of concentrations of glucose solution after plasma irradiation. Where the largest value in sensitivity was equal to 62.7 when the distance between electrodes was 5 cm compared to the sensitivity before irradiation, which was equal to 92. The high response showed in results demonstrating that the fabricated waveguide coated ZnO after plasma irradiation has the excellent potential application as a sensor to detect small concentration of glucose solution.